Creation of Accessories Shape of Buffalo Head with Source of Ideas for Unan-Unan Ceremony Using Waste Techniques - Aini, Qurrota; Nahari, Inty; Nashikhah, Ma’rifatun; Arifiana, Deny (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Along with the development of the industrial sector, without realizing it, this raises new problems, namely environmental pollution by liquid, solid, gas, and B3 (Toxic and Hazardous Materials) waste.  The purpose of this research is to increase the selling value of waste and manage waste so as not to pollute the environment.  This research uses the Practice-led Research method, which is a scientific work derived from ongoing practice research by creating new works through research and practice carried out On this occasion, the researcher will create an accessory made of styrofoam material and will be published in a Unesa Fashion Creation Title performance in 2023 which carries the big theme of BHUMIBRAMA. The result of this study is an accessory in the shape of a buffalo head with styrofoam as the main material.